2008
DOI: 10.1109/tcsii.2008.921411
|View full text |Cite
|
Sign up to set email alerts
|

Improved Bounds on the $L(2,1)$-Number of Direct and Strong Products of Graphs

Abstract: Abstract-The frequency assignment problem is to assign a frequency which is a nonnegative integer to each radio transmitter so that interfering transmitters are assigned frequencies whose separation is not in a set of disallowed separations. This frequency assignment problem can be modelled with vertex labelings of graphs. An (2 1)-labeling of a graph is a function from the vertex set ( ) to the set of all nonnegative integers such that ( ) . This paper considers the graph formed by the direct product and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The authors prove that for all the three classes of graphs the conjecture by Griggs and Yeh is true. In [164] the previous upper bounds for direct and strong product of graphs are improved. The main tool for this purpose is a more refined analysis of neighborhoods in product graphs.…”
Section: Product Of Paths Cycles and Cliquesmentioning
confidence: 99%
“…The authors prove that for all the three classes of graphs the conjecture by Griggs and Yeh is true. In [164] the previous upper bounds for direct and strong product of graphs are improved. The main tool for this purpose is a more refined analysis of neighborhoods in product graphs.…”
Section: Product Of Paths Cycles and Cliquesmentioning
confidence: 99%
“…The (2,1) L -labeling has been extensively studied in recent past by many researchers [see, 1,2,4,7,8,[14][15][16][17][18][19][20][21]. The common trend in most of the research paper is either to determine the value of (2,1) L -labeling number or to suggest bounds for particular classes of graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Klavzar and Spacepan [9] have shown that 2 ∆ -conjecture holds for graphs that are direct or strong products of nontrivial graphs. After that Shao, et al [15] have improved bounds on the (2,1) L -labeling number of direct and strong product of nontrivial graphs with refined approaches. Shao and Zhang [17] also consider the graph formed by the Cartesian sum of graphs and prove that the λ -number of (2,1) L -labeling of this graph satisfies the 2 ∆ -conjecture (with minor exceptions).…”
Section: Introductionmentioning
confidence: 99%
“…The L(2, 1)-labelling and the circular-L(2, 1)-labelling on products of graphs have been rather extensively studied in recent years [6,8,12,15,17,18].…”
Section: Introductionmentioning
confidence: 99%